Experience-based activities in a blended model Master’s degree - Ganino, Giovanni; La Vecchia, Loredana; Zappaterra, Tamara (Formazione & insegnamento, 2023)
During the previous academic year, the University of Ferrara implemented the blended mode Master’s Degree Course, titled “Formazione, comunicazione e cittadinanza digitale” (Training, Communication, and Digital Citizenship). This course was specifically designed to address the challenges presented by network technologies and the consequential changes in our society and daily lives. In light of these considerations, a didactic model was formulated, aiming to integrate theoretical and practical knowledge while fostering principles of responsibility and sustainability in students' learning and assessment processes. Central to this model is the concept of “authentic task,” which involves engaging students in activities that apply knowledge, cognitive abilities, and practical skills to real-world situations. By adopting a blended teaching approach, the course facilitates the development of transversal skills, as encouraged by authentic tasks. To gather feedback on this approach, a qualitative survey was conducted among the students enrolled in the degree course, aiming to explore their perspectives and perceptions regarding their learning experiences. This study contributes to the ongoing discourse on effective pedagogical strategies in the digital age.